The Reproductive Outcome in patients having Primary Infertility or Recurrent Miscarriages after performing Hysteroscopic Septal Resection - Ahmed Mahmoud Abdou; Moustafa Taha Abdelfattah (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2018)
Objective: To assess the reproductive outcome after hysteroscopic septal resection in women with unexplained infertility or recurrent miscarriage.  Design: Prospective clinical trial.  Setting: Zagazig university hospitals, Egypt. Patients: 47 patients (20 patients with primary infertility and 27 patients with recurrent miscarriage diagnosed to have uterine septum)  Intervention: hysteroscopic septal resection.  Main outcome measures: pregnancy rate and its outcome (miscarriage, preterm birth, term birth and live-birth rates).  Results: There was significant improvement in reproductive outcome in patients with primary infertility and uterine septum after hysteroscopic metroplasty; pregnancy rate was 55% (11 pregnancies out of 20 patients). Abortion and preterm labor rates were low (5 and 10% respectively) while term delivery and live-birth rates were high (40 and 45% respectively).